Analisis Pemahaman Mahasiswa Pba Stambuk 2020 Terhadap Nasikh Mansukh Dalam Studi Ilmu Al-Qur’an - Faisal Sahbudin; Muhammad Alfiansyah; Dedi Masri; Muhammad Rizky Nasution; Adila Umniati Aufa (Universitas Palan, 2023)
The purpose of this study was to find out how far the understanding of Nasikh and Mansukh by PBA Stambuk 2020 students. This study used a mixed research method, in which data collection was taken using a questionnaire or questionnaire method also using interviews to find research results in the form of descriptive interviews, . The results of the study show that the majority of PBA Stambuk 2020 students have a basic understanding of the Nasikh and Mansukh concepts. These students understand the terminology of Nasikh and Mansukh studies in the study of Al-Qur'an science. However, some students experience difficulties in understanding the study of history and the reasons behind the abolition or replacement of the syara' law or what is known as Nasikh and Mansukh.